THE EFFECTIVENESS ABSORPTION TEST OF LUBRICATING OIL WASTE AND HSD FUEL WITH NATURAL FIBERS (DURIAN SKIN) - Abdul Rahman; Wawan Kusdiana; Ayip Rivai; Heru Hadi Suseno (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
Pollution of sea water due to oil spills often occurs. Among them are tanker accidents, explosions of offshore oil platforms, ship operation errors and waste from the petroleum and coal industries. Oil spills in the sea often cause pollution which leads to damage to biological resources and damage to the underwater ecosystem. The purpose of this study was to determine the process and processing, and to determine the ability of durian skin to adsorb lubricating oil waste and HSD fuel. This research was conducted by processing the waste with variations of time 2, 5, and 10 minutes. And with variations in durian skin size of 0.25 mm², 1 mm², and 9 mm². With drying of durian skin between 1-15 days with 1-30 days. Then the results were analyzed to determine the efficiency of absorbing durian skin. The results of STTAL laboratory studies showed an increase in durian skin mass after undergoing a process of adsorption of lubricating oil waste and HSD fuel. Thus, the optimal durian skin time and size obtained on lubricating oil waste is 10 minutes with a surface area of 1 mm², mass of 4 grams in drying for 1-30 days. With efficiency of 82.54%. Whereas the HSD fuel is 10 minutes with a surface area of 0.25 mm², mass 4 grams on drying for 1-15 days. With an efficiency of 86.03%.Keywords: Durian skin, adsorption of lubricating oil waste, HSD